الإعلام الإسلامي: إشكالية المصطلح - علي سلطاني العاتري (International Institute of Islamic Thought, 2015)
تمثِّل العلوم الاجتماعية المعاصرة ذات المنشأ الغربي تحدياً للعلماء والباحثين المسلمين في جوانب متعددة، منها قضية المصطلح. ولمواجهة هذا التحدي جرت محاولات متعددة تحت عناوين مختلفة منها التأصيل والأسلمة. وواجهت هذه المحاولات معارضة شديدة من دعاة التماهي بالفكر الغربي، من جهة، كما واجهت نقداً من داخل الدائرة الإسلامية نفسها من جهة أخرى، لما رآه الناقدون من مظاهر الخلل والقصور. وميدان الإعلام واحد من ميادين العلوم الاجتماعية التي لا يزال المصطلح فيها يمثل مشكلة في جهود التأصيل وبناء الرؤية الإسلامية. وتهدف هذه الدراسة إلى مناقشة مصطلح "الإعلام الإسلامي" وما يثيره من إشكالات معرفية، وانعكاسات تطبيقية، جعلت المصطلح قاصراً عن أداء الوظيفة المنشودة منه في بناء العلم وتوظيفه في تحقيق مقاصد الإسلام في المجتمع البشري المعاصر. Contemporary social science with its Western-origin represents a challenge for Muslim scholars and researchers in various aspects, including the issue of terminology. To meet this challenge various attempts have been made under different titles, such as Islamization and establishing Islamic foundations. Such attempts has faced stiff opposition from advocates of identification with Western thought, on the one hand, and criticism from within the Islamic Circle itself on the other hand, because of what was seen as imbalance and deficiencies. Media is one of the fields of social science, in which the terminology is still a problem in building Islamic perspective and establishing Islamic foundations of the field. This study discusses the term "Islamic media", its epistemological problems, and practical implications; that makes the term unable to perform the desired function, especially in the construction of knowledge and using it to achieve Islamic objectives in the contemporary human society.